The Economics of Production in Chinsse Rubber Smallholdings in Peninsular Malaysia - Chew, Tek Ann (1981)
In this study standard production function techniques are used to analyse the economics of production in Chinese rubber smallholdings in Peninsular Malaysia. The data used were taken from two surveys, the 1963/64 RRI Survey and the 1978 Survey conducted by the author in the state of Selangor. Considering the importance of the rubber smallholding sector in the Malaysian economy, it is surprising that there has been only one production function study on rubber smallholdings in Malaysia thus far. The probable reason for dearth of research in this area is the difficulty in handling the perennial nature of the rubber tree. A variable must be specified to capture the capital service flow accruing from the live capital tree-stock. In this thesis, "expected yields" estimated from yield profiles of various clonal material are used as proxies for the capital service flows. The yield profiles were drawn from published yield records of various selected commercial estates. Estates are more advanced technologically in rubber production than smallholdings. Thus the "expected yields" estimated will be higher than the real capital service flows.